Rhetorical styles of Introduction in English language teaching (ELT) research articles - Rochma, Anis Firdatul; Triastuti, Anita; Ashadi, A. (Indonesian Journal of Applied Linguistics, 2020)
Research articles have been considered as the primary media of knowledge production. Nevertheless, for some undergraduate students, writing a research article can be a challenging task since they need to be aware of its rhetorical styles. Even though previous studies have been conducted to reveal the rhetorical styles of scientific papers, yet tend to focus more on research articles obtained from well-established journals. Hence, this study aims to reveal the rhetorical styles and draw the rhetoric pattern from the introduction section of 73 research articles written by the undergraduate students of English Language Education (ELE) at a state university in Yogyakarta. This is a qualitative investigation whose data were collected by random sampling technique and went through Safnil’s (2013) four analysis stages. As the primary framework for analysis, the modified CARS (Create a Research Space) model (Swales Feak, 2004) was adopted. The results show that Step 2: Making topic generalization in Move 1 and Step 1B: Indicating a gap in Move 2 are the obligatory steps in writing the introduction section. Nevertheless, the results reveal that mostly undergraduate research papers lack 1 step in Move 1, 2 steps in Move 2, and 3 steps in Move 3. The omission of steps in the CARS model by these student-authors seems to happen due to two major factors, namely the scarcity of control over the writing process and linguistic resources, hence suggesting pedagogical implications for academic writing courses.